Do you care your local language? - Isna Indriati (Journal on English as a Foreign Language, 2014)
The blooming of the English usage every time and everywhere may exterminate the use of local languages. It is also supported by the increase of migration out of or into areas of Indonesia that makes people tend to use Indonesian often than local languages. This might be caused by the personal inability to communicate with indigenous people by their native languages. Besides, the cross cultural marriage also results on the difficulties to determine which mother tongue they introduce to their children. In fact, multicultural condition demands people to use Indonesian frequently. This condition shows that Indonesian works greatly because it is national language. In contrast, the interest of using and learning local language may decrease gradually. This study was conducted to find out whether Indonesian EFL learners of Dayakese background have highly concern to their local language. The data were gathered through direct observation, interviews, and questionnaire. The data collected, then, were analyzed rigorously using descriptive statistics. The findings show that most students have low affection towards their local language, even those who are from indigenous people. Local language is less valued than Indonesian, since they are from different ethnic. Indonesian, then, is highly valued for both formal and informal communication, whether or not it is used as language learning instruction. It is recommended that there is a need for the government to encourage the use or learning of local language. Further, the educational language policy makers together with the Art and Tourism Department consider the promoting local language as a language instruction and a subject. Thus, there will be any ways to keep the ethnicity of Indonesia.